2007
DOI: 10.1016/j.jcrysgro.2006.10.131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of InGaN/GaN MQW hydrogen treatment and threading dislocation optimization on GaN LED efficiency

Abstract: We report on the effect of GaN buffer threading dislocation (TD) optimization and InGaN/GaN quantum well (QW) hydrogen ðH 2 Þ treatment on the efficiency of GaN light emitting diodes (LEDs) operating in the spectral range from 400 to 500 nm. A tenfold reduction of the TD density in the GaN buffer increased the efficiency of blue LEDs operating at high current density, while in green LEDs it had very little effect. The reduced TD density also increased the compressive strain in the InGaN QWs, and caused blue sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Several previous works reported that growth interruption 16 or introduction of H 2 after the growth of InGaN well layer 27,28 can remove In-rich InGaN clusters on the InGaN QW upper interface and enhance the thermal stability of InGaN well layer. However these approaches may blueshift the emission wavelength greatly which needs to be avoided when growing green InGaN LDs.…”
mentioning
confidence: 99%
“…Several previous works reported that growth interruption 16 or introduction of H 2 after the growth of InGaN well layer 27,28 can remove In-rich InGaN clusters on the InGaN QW upper interface and enhance the thermal stability of InGaN well layer. However these approaches may blueshift the emission wavelength greatly which needs to be avoided when growing green InGaN LDs.…”
mentioning
confidence: 99%
“…GaN-based light emitting diodes (LEDs) have been widely studied for their great advantages in solid state lighting and display, among which blue LEDs, whose internal quantum efficiency (IQE) values can exceed 90%, have achieved great success attributed to the improvement of epitaxy growth technology and device structures [1][2][3][4][5][6][7][8]. However, the IQE values of green LEDs are still relatively low since the difficulty of growing high-quality single crystal caused by huge lattice mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all of the GaN-based devices are hetero-epitaxially grown on foreign substrates due to the lack of GaN substrates for homo-epitaxy. The performances of these devices are greatly decreased because of the high threading dislocation density caused by the large lattice and thermal expansion coefficient mismatches between the foreign substrates and GaN epitaxial layer 4 .…”
Section: Introductionmentioning
confidence: 99%